Frontline meetings as support for cross-boundary coordination in hospitals. Issue 7 (28th November 2019) - Prætorius, Thim; Hasle, Peter
Abstract : Purpose: The purpose of this paper is to investigate frontline meetings in hospitals and how they are used for coordination of daily operations across organizational and occupational boundaries. Design/methodology/approach: An in-depth multiple-case study of four purposefully selected departments from four different hospitals is conducted. The selected cases had actively developed and embedded scheduled meetings as structural means to achieve coordination of daily operations. Findings: Health care professionals and managers, next to their traditional mono-professional meetings (e.g. doctors or nurses), develop additional operational, daily meetings such as work-shift meetings, huddles and hand-off meetings to solve concrete care tasks. These new types of meetings are typically short, task focussed, led by a chair and often inter-disciplinary. The meetings secure a personal proximity which the increased dependency on hospital-wide IT solutions cannot. During meetings, objects and representations (e.g. monitors, whiteboards or paper cards) create a needed gathering point to span across boundaries. As regards embedding meetings, local engagement helps contextualizing meetings and solving concrete care tasks, thereby making health care professionals more likely to value these daily meeting spaces. Practical implications: Health care professionals and managers can use formal meeting spaces aided by objects and representations to support solving daily and interdependent health care tasks in ways that IT solutions in hospitals do not offer today. Implementation requires local engagement and contextualization. Originality/value: This research paper shows the importance of daily, operational hospital meetings for frontline coordination. Organizational meetings are a prevalent collaborative activity, yet scarcely researched organizational phenomenon.